2019
DOI: 10.1155/2019/1085172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Radio Frequency Cold Plasma Treatment on Intermediate Wheatgrass (Thinopyrum intermedium) Flour and Dough Properties in Comparison to Hard and Soft Wheat (Triticum aestivum L.)

Abstract: Cold plasma is an emerging technology to improve microbiological safety as well as functionality of foods. This study compared the effect of radio frequency cold plasma on flour and dough properties of three members of the Triticeae tribe, soft as well as hard wheat (Triticum aestivum L.) and intermediate wheatgrass (Thinopyrum intermedium, IWG). These three flour types differ in their protein content and composition and were evaluated for their solubility, solvent retention capacity, starch damage, GlutoPeak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 35 publications
3
27
1
Order By: Relevance
“…The increases in starch contents coincided with increases in starch damage, which ranged from 3.04% ± 0.10% to 8.78% ± 0.24% (Figure 1a,b). While the values at the low range were in line with previous reports [17], and comparable to some soft wheat varieties [18,19] or rye [15], the values at the upper range were closer to medium-hard [20] or even hard wheat varieties [21]. Different from the compositional attributes shown in Table 3, tempering temperature caused more differences among samples.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The increases in starch contents coincided with increases in starch damage, which ranged from 3.04% ± 0.10% to 8.78% ± 0.24% (Figure 1a,b). While the values at the low range were in line with previous reports [17], and comparable to some soft wheat varieties [18,19] or rye [15], the values at the upper range were closer to medium-hard [20] or even hard wheat varieties [21]. Different from the compositional attributes shown in Table 3, tempering temperature caused more differences among samples.…”
Section: Resultssupporting
confidence: 89%
“…For samples tempered at 30 °C for 4 or 24 h, as well as samples tempered at 45 °C for 4 or 8 h, nontempered controls had significantly lower lactic acid SRCs than samples of 12% or 14% target moisture (Table 4). While the lactic acid SRC values were lower than for hard wheat, they were higher than previously reported for refined IWG [17]. This indicates that when the extent of refinement is increased, IWG flours develop stronger protein networks, which would be beneficial for the manufacture of products that require gas holding properties.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The MT (Table 1) and AE (Table ) values reported in the current study were also higher than the values reported by Held et al. (2019) for refined IWG (MT ~35 BE, AE = 678 BU) flour obtained without using tempering as a pretreatment step before refinement. It is important to note that Held et al.…”
Section: Resultscontrasting
confidence: 74%
“…Hence, there are different areas of their potential application. Recently reported plasmas [18][19][20][21][22][23][24] resemble LPGP neither in the methods of their generation nor in their character.…”
Section: Introductionmentioning
confidence: 99%